6. Penggunaan Bahan Alam Untuk Meningkatkan Keterampilan Membuat Mozaik Dalam Tema Lingkungan Bersih, Sehat Dan Asri Pada Siswa Sekolah Dasar - Yuliati, Ida; ., Suprayitno (JURNAL WAHANA PENDIDIKAN DASAR, 2017)
Teachers hold a primary quality-control in each lesson. Teachers must be able to provide learning as attractive as possible so that students are not bored while they are in class. At the time of learning SBdP particularly craft-making subject in making mosaic, the interesting learning has been carried out by researchers as a first grade teacher at SDN Putat Jaya I / 377. The problem that occurs is the students? mosaic works are still less neat and even there are still many students who have not finished it yet to the time being provided. This is because the students have not been given the opportunity to directly practice in creating mosaics by using the other substances instead of paper (in this case natural substances) to create works that always ultimately having short of time because they have to cut up the paper first. From the above-stated problems, the researchers propose the improvements such as the use of natural substances in mosaic craft substances subject. The purpose of this research  is (1) to describe teachers? activity in the implementing the craft learning by using natural substances to improve the students? skills of making mosaics grade 1 SDN Putat Jaya I / 377 Surabaya (2) to describe students? activity in implementing the craft learning by using natural substances to improve the skills of making mosaic of the first grade students of SDN Putat Jaya I / 377 Surabaya (3) to describe the improvement of the skills to make a mosaic on the first grade students of SDN Putat Jaya I / 377 in implementing the craft-learning by using natural substances. This study uses classroom action research design, which is conducted in two cycles. Each cycle consists of four phases: planning, implementation, observation, and reflection. The subjects of this study were students of first years of SDN Putat Jaya I / 377 Surabaya consisting of 37 students. The results shows that (1) teachers? activities in the first cycle obtains the achievement score 71.6%, the second cycle has reached 81.8% (2) activities in the first cycle obtains the achievement score 73.8%, the second cycle has reached 85% (3) The students? skill in the first cycle obtains an average of 7.18 with a percentage classical completeness is 62.2%, the second cycle classical average of 7.78, with a percentage of 81.1% completeness. From the above results, it can be concluded that the use of natural substances can improve the skills of making mosaics in the first grade students of SDN Putat Jaya I / 377 Surabaya.